STUDI PERISTIWA TRAGEDI SARINAH TERHADAP PASAR MODAL INDONESIA - Arde, M.Hatta Diman; Kesuma, Ketut Wijaya (E-Jurnal Manajemen, 2017)
This study aims to know the Indonesian capital market reaction to the attack on Sarinah area by looking at the average abnormal return and the difference in the average abnormal return before the event and after the attack in the region Sarinah. This study uses a sample of 45 companies listed in the LQ45 index period August 2015 to in January 2016. The data were analyzed with a mean adjusted model approach is used to find abnormal returns, subsequent test results of data analysis using t-test and paired sample t-test , The study found that there is a negative market reaction occurs on D+5, D+4, D+2, D+1, D0, D-3 and D-5 evidenced by the average abnormal return is statistically significant. Furthermore, the test results data using paired samples t-test showed that there is no significant difference between the average abnormal return obtained all companies listed in LQ45 index in the Indonesia Stock Exchange before and after the attack in the region Sarinah.
Keywords: Market Reaction, Abnormal Return.